2022
DOI: 10.1097/md.0000000000030838
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of job-related psychological flexibility, coping style and personality types in depression in Chinese physicians: A cross-section study

Abstract: To investigate the associations of job-related psychological flexibility, coping style and personality types with and their interactions in depression in Chinese physicians. A cross-sectional survey of 444 physicians was conducted by using the convenience sampling method in the municipal hospitals in Zhengzhou, Henan province. Center for Epidemiological Studies Depression, Work-related Acceptance and Action Questionnaire, the Simplified Coping Style Questionnaire and Eysenck Personality Questionnaire-Revision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…A rich body of literature has substantiated the relationship between professional title and mental health. [45][46][47] The present study revealed that HCPs with intermediate professional titles had a significantly greater proportion of depression than those with junior professional titles, which is consistent with past research. 45 47 This association may be attributed to HCPs with intermediate professional titles often having more frequent night shifts and greater responsibilities in medical aid tasks.…”
Section: Open Accesssupporting
confidence: 92%
“…A rich body of literature has substantiated the relationship between professional title and mental health. [45][46][47] The present study revealed that HCPs with intermediate professional titles had a significantly greater proportion of depression than those with junior professional titles, which is consistent with past research. 45 47 This association may be attributed to HCPs with intermediate professional titles often having more frequent night shifts and greater responsibilities in medical aid tasks.…”
Section: Open Accesssupporting
confidence: 92%
“…Self-realization is considered as a motivation that can regulate human behavior and the level of development to be achieved [5]. Positive feedback accompanied by high job acceptance will make commitment and work appreciation higher, deep realizing the value of life [23].…”
Section: Resultsmentioning
confidence: 99%
“…Like resilience, PF is a malleable factor and is a key target for psychological intervention 33 , 34 . Promisingly, high PF is associated with better quality of life in healthcare professionals 35 although very little research has focused specifically on surgeons 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%